Analysis of the sources of inflation in Iraq using the autoregressive distributed lag (ARDL) model for the period 1990-2016 - Kadhim Saad Abdul Reda (Iraqi Journal for Administrative Sciences, 2024)
Inflation Phenomenon became evokes attentions of researchers and writers across different tenses in order to knowing the reasons that stand beyond creating this problem as well as its effects and then results which will appear later . there for whole world became looking for find the solutions and treatments for this problem regardless about economic regimes or developing levels that accurse in any country . because all them are suffering from this problem. So that arraigns monetary policy to study this problem and explains its implications . In under developing countries and Iraq is one of them inflation Phenomenon reflects their peculiarity which characterizes by entangle and complex , where these Phenomenon considers one of obstacles which confront development process. There are many reasons for create Inflation one of them are imports which lead to imported inflation because of state depend on importing in order to meet local demand if its transactions was with states Suffer from inflation. The research aims to seek the reasons of inflation in Iraq after 2003 . and investigate rang sharing of imports in creating inflation pressure , where as it is known Iraq depend on imports vastly for facing increasing local demand . Also the research based on basic hypothesis indicates the imports share actively in booster inflationary pressures and push the prices to rise .